2009
DOI: 10.1039/b822325d
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency and stable dye-sensitized solar cells with an organic chromophore featuring a binary π-conjugated spacer

Abstract: We employed a binary spacer of orderly conjugated 3,4-ethyldioxythiophene and thienothiophene to construct a wide-spectral response organic chromophore for dye-sensitized solar cells, exhibiting a high power conversion efficiency of 9.8% measured under irradiation of 100 mW cm(-2) air mass 1.5 global (AM1.5G) sunlight and an excellent stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
337
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(353 citation statements)
references
References 27 publications
12
337
0
4
Order By: Relevance
“…For the TPA organic dyes, experimental and theoretical investigations have demonstrated two allowed excited states characterized by large transition probabilities appearing in the UV/Vis region. [21,32] Our simulated results of the acene-modified TPA dyes show the experimental phenomenon, with a first intense peak in the 400-700 nm region and a second peak around 300 nm.…”
Section: Uv/visible and Fluorescence Spectrum Propertiessupporting
confidence: 68%
See 2 more Smart Citations
“…For the TPA organic dyes, experimental and theoretical investigations have demonstrated two allowed excited states characterized by large transition probabilities appearing in the UV/Vis region. [21,32] Our simulated results of the acene-modified TPA dyes show the experimental phenomenon, with a first intense peak in the 400-700 nm region and a second peak around 300 nm.…”
Section: Uv/visible and Fluorescence Spectrum Propertiessupporting
confidence: 68%
“…In addition, such orbital photoexcitation features also slow down the recombination of injected electrons in TiO 2 with oxidized dye molecules due to their remoteness. [21] V OC , the energy difference between the redox potential of the electrolyte and the quasi-Fermi level of the electron in the TiO 2 conduction band, is a key parameter for the h of DSSCs. The semiconductor conduction band shift (with respect to the electrolyte redox potential, Dc) can be expressed as a function of the dipole moment of adsorbed dye [Eq.…”
Section: Tpa Dyes On Tio 2 Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, los colorantes orgánicos no sólo resultan más económicos, también alcanzan una eficiencia alrededor de 9.8%. 7 Sin embargo, la desventaja de los colorantes orgánicos son los problemas asociados con la complejidad de las rutas sintéticas.…”
Section: Introductionunclassified
“…Zhang et al [7] reported that DSSCs based on a D-p-A dye (C217) show a power conversion efficiency of 9.8%.…”
Section: Introductionmentioning
confidence: 99%